The Effect of Internal Control and Compensation on the Trend of Accounting Fraud in Retail Companies in Ternate - Muhammad Hi Hasan (Peneliti.net, 2021)
This study aims to determine the effect of internal control, compliance with accounting rules, and unethical behavior on the tendency of accounting fraud. The population in this study is a state-owned company in Ternate City. The sampling technique uses total sampling. The data of this study were obtained from the leadership and accounting staff. The type of data used is primary data. The method of data collection is a survey, using a questionnaire. The analysis tool uses multiple linear regression. Statistical analysis found that: 1) the effectiveness of internal control has a significant negative effect on the tendency of accounting fraud, where the significance value is 0.040 <α0.05 and -0.295 (H1 is accepted), 2) the adherence to accounting rules is negatively significant to the tendency of accounting fraud where the significance value is 0.045 <α0.05 and -0.253 (H2 accepted), 3) unethical behavior has a significant positive effect on the tendency of accounting fraud, where the significance value is 0.046 <α0.05 and 0.276 (H3 is accepted). The results showed that the effectiveness of internal control and compliance with accounting rules was significantly negative on the tendency of accounting fraud, while unethical behavior was significantly positive on the tendency of accounting fraud